Teachers' perceptions of implementation of aided AAC to support expressive communication in South African special schools: a pilot investigation. (1st October 2016) - Tönsing, Kerstin M.; Dada, Shakila
Abstract: Although the provision of assistive technology for students with disabilities has been mandated in South African education policy documents, limited data are available on the implementation of aided augmentative and alternative communication (AAC) in classrooms. This pilot investigation used a concurrent mixed-methods survey design to determine the extent to which aided AAC was implemented to foster students' expressive communication in preschool to Grade 3 classrooms in special schools from six urban school districts in the Gauteng (the smallest, most affluent and most densely populated of the nine South African provinces), and also obtained teachers' perceptions of this process. A total of 26 teachers who taught students who used aided AAC for expression participated. Although there is evidence of provision and also implementation of aided AAC in classrooms, various limitations still exist. Teachers identified an array of factors that influenced the implementation of aided AAC, including those related to themselves, the classroom context, the characteristics of aided AAC, students using AAC, and other stakeholders. These factors are discussed in the light of international literature as well as the local context, and are used as a basis to suggest a research agenda for AAC in the South African education system.